Effects of Dietary Supplementation of Soy Isoflavones on the Performance and Egg Quality in Native Chinese Breeder Hens - E Abdelghani; W Xing; Y Li; D Shen; MA Alsiddig; C Li (Brazilian Journal of Poultry Science, 2019)
ABSTRACT To investigate the effects of soy isoflavones (ISF) on the laying performance of Xueshan breeder hens at different phases of the egg production cycle, 32 weeks (wks) old local Chinese breeder hens were assigned to two groups with three replicates (750 hens/replicate) for control and treatment groups. Then every group was divided into three sub-groups following 4, 12, and 20 wks administration of control or ISF diet. General Linear Model procedure was used (2× 3), and treatments were considered of two factors (diets and time) with different levels (control and ISF diets; 4, 12, and 20 wks of diet supply time). Basal diet with 3 mg/kg ISF was used. Performance, egg quality, organs relative weight and cholesterol level were measured at three time-points of 36, 44, and 52-wks of age old. The results showed that both diets and time significantly affected the production performance and physiological parameters. In details, ISF inclusion significantly (p=0.02) decreased average egg weight and average feed intake compared to control at 52-wks of age old, however, feed conversation ratio was not affected by ISF diet. Moreover, ISF diet caused to an increase hatching rate (p=0.01) at 36-wks old hens, an abnormal egg rate decrease (p=0.02) at 44-wks old, an increase in yolk color (p=0.035) and Haugh unit (p=0.039), and a decrease in low-density lipoprotein cholesterol level (p=0.03) at 52-wks of age old. ISF diet also increased spleen relative weight (p=0.041) and total antioxidant capacity compared to the control group. The results revealed that ISF inclusion exerted some benefits, thus it could be a potential feed additive for the breeder hens.